2014
DOI: 10.1016/j.heares.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention, selective attention and cognitive control in deaf and hearing children

Abstract: Deaf children have been characterized as being impulsive, distractible, and unable to sustain attention. However, past research has tested deaf children born to hearing parents who are likely to have experienced language delays. The purpose of this study was to determine whether an absence of auditory input modulates attentional problems in deaf children with no delayed exposure to language. Two versions of a continuous performance test were administered to 37 deaf children born to Deaf parents and 60 hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 56 publications
6
100
0
5
Order By: Relevance
“…Interestingly, a recent study comparing deaf and hearing children in a continuous performance test (Dye & Hauser, 2014) provides indirect evidence for the existence of such top-down modifications in the deaf population. Dye and Hauser (2014) showed that young deaf children (6-8 years old) were more distracted by peripheral visual distractors compared to hearing children, but the disadvantage in performance vanished in the older deaf group (9-13 years old) (Dye & Hauser, 2014).…”
Section: Possible Plastic Modifications Underlying the Present Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study comparing deaf and hearing children in a continuous performance test (Dye & Hauser, 2014) provides indirect evidence for the existence of such top-down modifications in the deaf population. Dye and Hauser (2014) showed that young deaf children (6-8 years old) were more distracted by peripheral visual distractors compared to hearing children, but the disadvantage in performance vanished in the older deaf group (9-13 years old) (Dye & Hauser, 2014).…”
Section: Possible Plastic Modifications Underlying the Present Resultsmentioning
confidence: 99%
“…The documented delay in oculomotor behavior of deaf adults may be the result of an adaptive outcome of deafness-related plasticity aimed at avoiding potentially disruptive capture by irrelevant salient peripheral visual stimuli in the environment (see also Dye and Hauser (2014) for converging conclusions). This adaptation would allow for a more controlled deployment of selection and would benefit the efficiency of visual information processing in deaf individuals.…”
Section: Control Over Stimulus-driven Behaviormentioning
confidence: 99%
“…This was included, as it is well known that vestibular impairments (that can lead to vertigo) are frequently associated with hearing difficulties (odds ratio of 1.9-2.3 [56,57]. It has also been shown that D/HOH persons might develop different attentional abilities (e.g., enhanced peripheral visual attention) [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, along the lines of Dye and Hauser (2014), Horn, Davis et al (2005) and Yucel and Derim (2008) it is important to note the high percentage of classroom teachers and speech, language and hearing specialist teachers who expressed that the implanted students displayed difficulties to stay attentive throughout the completion of tasks. Some studies (Quittner et al, 2007, Quittner et al 1994Smith, Quittner et al1998) suggest that even though in the months following implantation there are substantial improvements in the tasks that require greater and sustained visual attention, it is not until the children have reached 8 or 9 years of age that they are able to make better use of the cochlear implant due to the strong relationship that exists between the level of performance required in each task and the age of the children.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of this, and although it may seem that implantation favors a better integration within the school context, many students with cochlear implants reject interactions with their peers, even though they have their initial acceptance. This may be due to their inability to interact verbally at the same pace as their peers, which consequently limits opportunities to develop similar prosocial skills and behaviors (Dye & Hauser, 2014;Punch & Hyde, 2010). Schorr (2005) stated that boys and girls between the ages of 5 and 9 experienced the same level of solitude as hearing children of the same age.…”
Section: Introductionmentioning
confidence: 99%